The mediating role of hospital image: The impact of care cost and service quality on patient satisfaction - Firas AlOmari (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
The primary goal of this research is to empirically examine the function of hospital image in mediating the relationship between care cost, healthcare service quality, and patient satisfaction. Eight hospitals in the Syrian capital, Damascus, were chosen to conduct this research. The patients were selected based on a random sampling method. As a result, N=270 questionnaires were considered for statistical analysis and testing of the proposed model. Furthermore, patients regularly admitted to the hospital were chosen to have more experience with the services delivered by the related healthcare provider. The statistical results indicated that the hospital image partially mediates the relationship between financial factors, service quality (medical staff caring, procedural process, and tangibility), and patient satisfaction. Interestingly, our result highlighted that care cost (β= 0.472) has more influence on hospital image than service quality (β= 0.307), while service quality (β= 0.431) has more effect on patient satisfaction than care cost (β= 0.259). Our results illustrated the significance of reducing care costs, increasing consultation time, and minimizing waiting time, to increase patient satisfaction and improve hospital image. Our study calls on hospital managers in the healthcare sector not to sacrifice the quality of care at the expense of care costs.